2022
DOI: 10.1155/2022/5902445
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Model on Network Public Opinion Communication Model of Major Public Health Emergency and Management System Design

Abstract: In order to identify the communication law of network public opinion in major public health emergency, a multifactor communication model based on multiagent modeling is proposed. Based on the SEIR model and NetLogo simulation analysis, the model integrates a variety of network public opinion communication characteristics and extends the existing single network public opinion communication model. Based on these studies, a network public opinion communication management system is designed and developed with Pyth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Here, equation ( 9) represents the value of the input index and p is the unit value of the decision; formula (10) represents the output value and the unit value determined by p; formula (11) represents the value of the input index and the cell value of model j; formula (12) represents the output value and the j-type cell value [12]. e generalized CCR model for decision unit p is as follows:…”
Section: Improved Dea Algorithm and Classification Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, equation ( 9) represents the value of the input index and p is the unit value of the decision; formula (10) represents the output value and the unit value determined by p; formula (11) represents the value of the input index and the cell value of model j; formula (12) represents the output value and the j-type cell value [12]. e generalized CCR model for decision unit p is as follows:…”
Section: Improved Dea Algorithm and Classification Algorithmmentioning
confidence: 99%
“…They believe that the production efficiency of most listed coal enterprises is acceptable, but there are great individual differences. Many enterprises still have great room for improvement and put forward suggestions to the administrative departments [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Te increasing popularity of the Internet and the number of netizens make society enter the information explosion era. Because the public opinion environment of the social networking platform is more open, free, and private than that of real society, and because public publishing and obtaining information in the network is more convenient and faster than exploring, publicizing, or querying information in the real world, more and more people pay attention to daily hot spots or public events through the Internet [1][2][3][4][5]. When people fnd the information they are interested in in the process of browsing the Internet, many people will express their own opinions and opinions on the content of the information, and the information containing the emotional tendencies and subjective attitudes of netizens constitutes a new network public opinion information [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…It is also a disease of unknown cause to public health in groups, major occupational or food poisoning, or other events that seriously affect public life and property ( 1 ). And it is characterized by suddenness, urgency, uncertainty, multiple subjects, and social impact ( 2 4 ). The novel coronavirus, first identified in late 2019, is a major public health emergency, and by the end of November 2022, the World Health Organization reported that the total number of new coronavirus pneumonia (COVID-19) cases had exceeded 625 million, with ~15 million direct and indirect deaths due to new coronaviruses ( 5 ), which are still spreading globally.…”
Section: Introductionmentioning
confidence: 99%